Our experiences with human body composition estimations; low discriminatory power of body mass index to segregate body fatness - Dandinasivara Venkateshaiah, Muralidhara; Ahmad Zubaidi, A.Latif; Mohd Nasir, Mat Nor (Malaysian Public Health Physicians Association, 2016)
Body mass index, though globally a very popular and frequently used surrogate measure of body fatness, has come under some scrutiny and serious criticism in recent years for its inability to reflect the same. This is particularly disconcerting with health risks involved in cardiometabolic diseases associated with obesity. Therefore, it is suggested that actual measurement of body fat levels be used and there are simple and easier techniques available. The measurements of body volume index in replacing body mass index may provide better information on human body composition for future research.